4.
a)
[tex]7 + 3x = 2(4 - x) \\ 7 + 3x = 8 - 2x \\ 5x = 2 \\ x = 0.4[/tex]
b)
[tex]4(6 - x) = 2(x - 3) \\ 24 - 4x = 2x - 6 \\ - 6x = - 30 \\ x = 5[/tex]
c)
[tex]0.5x + 20 = 4.4x \\ - 3.9x = - 20 \\ x = 5 \frac{5}{39} [/tex]
d)
[tex]20 + x = 20 - (20 - (20 - x)) \\ 20 + x = 20 - (20 - 20 + x) \\ 20 + x = 20 - 20 + 20 - x \\ 2x = 0 \\ x = 0[/tex]
5.
a)
[tex]5(x - 7) + 2 = - 28 \\ 5x - 35 + 2 = - 28 \\ 5x = 5 \\ x = 1[/tex]
b)
[tex]2(x - 1) + 3(x + 1) = 26 \\ 2x -2 + 3x + 3 = 26 \\ 5x = 25 \\ x = 5[/tex]
c)
[tex]4(3 - x) + 9 = 7(2 + x) + 29 \\ 12 - 4x + 9 = 14 + 7x + 29 \\ - 11x = 22 \\ x = - 2[/tex]
d)
[tex]9 = 5x + 6 - 5(x - 0.6) \\ 9 = 5x + 6 - 5x + 3 \\ 0 = 0[/tex]
Równanie tożsamościowe